Psychological Variables Underlying Cooperative Behavior for Local Communities: The Case of Regional Charismas in Japan (Global Journal of Human-Social Science, 2014)
Many empirical findings have shown that local communities can be improved if at least one altruistic person engages in cooperative behavior for the benefit of the community, as in the case of "The 100 charisma ambassadors of tourism" in Japan. This paper conducted a multilevel analysis to elucidate the psychological variables underlying such cooperative behavior (CB). A questionnaire survey was conducted using items previously proposed for measuring determinant factors of CB. The respondents were: "the 100 charisma ambassadors of tourism" (n = 95), residents living in the same region as the charismas (n = 400), and residents living in other regions (n = 500). By comparing different groups, personality and environmental factors promoting CB were examined. The results indicate that Schwartz's norm-activation factors contribute to the personality characteristics of the charismas, and that feelings of sympathy among residents contribute to the environmental characteristics of the locality of the charismas.
Keywords: altruistic motivation; cooperative behavior; charisma ambassadors of tourism; volunteer’s dilemma